The circuitry between ribosome biogenesis and translation in stem cell function and ageing. (July 2020) - Sharifi, Samim; da Costa, Hugo Filipe Rangel; Bierhoff, Holger
Highlights: Quiescent adult stem cells have considerable ribosome biogenesis, but low translational activity. Stemness depends on balancing ribosome biogenesis and translation. Stem cell ageing can cause elevation of rRNA and protein synthesis that drives proliferation and expansion of clones with reduced potency. Senescence of (very) old stem cells is associated with the shutdown of ribosome biogenesis. Abstract: Ribosome biogenesis takes place mainly in the nucleolus, a nuclear, non-membrane bound organelle forming around the gene arrays encoding ribosomal RNA (rRNA). Nucleolar activity comprises synthesis, processing and maturation of rRNAs, followed by their assembly with ribosomal proteins into pre-ribosomal particles. The final formation of translation-competent ribosomes in the cytoplasm is the prerequisite for protein synthesis, which is the most energy-consuming cellular process. In adult stem cells, ribosome biogenesis and protein synthesis determine the switch between the quiescent and the activated state, but also decide whether activated stem cells self-renew or differentiate. Given this major impact on cellular function, it seems likely that perturbations of the circuitry between nucleolar activity and translation lead to ageing-related stem cell deterioration. This review provides an overview of how ribosome biogenesis and translation govern stem cell function and discusses the resultant implication in stem cell ageing.